Caractérisation de la résistance au froid de deux espèces sclérophylles méditerranéennes par la fluorescence de la chlorophylle - Méthy, M; Trabaud, L (Ann. For. Sci., 1990)
Frost resistance characterisation of two mediterranean sclerophyllous species by chlorophyll fluorescence. Frost resistance of the photosynthetic system of 2 sclerophyllous species of the mediterranean region, Quercus ilex and Quercus coccifera, has been analysed. Measurements were made on 1 year and 1 month old leaves by the chlorophyll fluorescence induction method. Photosynthetic activity is inhibited very quickly for both the 2 species at the development stages studied. The photosynthetic system of Q ilex seems to be the most resistant but is destroyed after half an hour of exposure to cold at -20 °C, without any recovery after treatment. The effect of winter temperatures on the distribution areas of Q ilex and Q coccifera is discussed.
Keywords: chlorophyll fluorescence; Freezing; Quercus coccifera; Quercus ilex; Sclerophyll